Preventing Bullying Through Islamic Religious Education in Indonesian Elementary Schools - Bachrul Ulum; Leny Suryaning Astutik; Dwi Agustina Rahayu; A.A. Putu Eka Putra; Moh. Zaini (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study examines how Islamic Religious Education ( ) is implemented to prevent bullying in elementary schools. It focuses on value integration in instruction, Islamic habituation, and the role of teachers as moral mediators. Methodology: A qualitative multi-site case study was conducted in three elementary schools in Tulungagung Regency representing urban, semi-urban, and rural contexts. Data were collected from 3 principals, 6 teachers, and 15 Grade IV–VI students through interviews, participatory observation, and documentation. The interactive model of Miles, Huberman, and Saldaña was used for analysis. Main Findings: Three findings emerged. First, the integration of ukhuwah, tawadhu', and rahmah values into instruction built students' anti-violence awareness. Second, Islamic habituation programmes reduced verbal aggression consistently. Third, teachers' competency served as the key determinant of programme success. Novelty/Originality of this study: This study introduces a three-layer implementative model curricular integration, institutional habituation, and teacher mediation that extends the whole-school approach with a spiritual- teacher dimension. It also identifies Islamic-based restorative dialogue as a distinctive mediation technique not previously documented in -based bullying prevention literature.